Equations of dynamic method for a satellite in near-parabolic orbits - Petroškevičius, Petras (Geodesy and Cartography, 2012)
Satellite geodesy equations of dynamic method, suitable for near-parabolic orbits of artificial satellites of the Earth are given in the paper. By the observed satellite topocentric coordinates, it is possible to specify zonal and non-zonal coefficients of geopotential and elements of satellite orbit. Instead of time a new variable is used in equations related to real anomaly of parabolic movement with the same distance of perigee as satellite movement. Coefficients of equations are equations are expressed by (1-e)/2 size power series. Power series converge absolutely with eccentricity of satellite orbit value e from 0 to 1. When eccentricity value approaches to one, the velocity of series convergence is increasing.Article in Lithuanian.Dinaminio metodo lygtys, kai palydovo orbita artima paraboleiSantrauka. Gautos kosminės geodezijos dinaminio metodo lygtys. Taikant šias lygtis, pagal išmatuotas palydovo topocentrines koordinates galima patikslinti geopotencialo zoninius ir nezoninius koeficientus, punktų geocentrines koordinates bei palydovo orbitos elementus. Lygtyse vietoje laiko taikomas kintamasis σ0, siejamas su parabolinio judėjimo, kurio perigėjaus nuotolis tas pats kaip ir palydovo judėjimo, tikrąja anomalija v0, σ0 = tg v0/2. Lygčiu koeficientai išreikšti dydžio γ = 1–e/2 laipsninemis eilutemis. Čia e – orbitos ekscentricitetas. Eilutes absoliučiai konverguoja esant ivairioms palydovo orbitos ekscentriciteto reikšmems nuo 0 iki 1. Eilutes galima taikyti, kai |σ0 √γ |